2020
DOI: 10.1080/19401493.2020.1832148
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a reduced training subspace on the prediction accuracy of neural networks for hygrothermal predictions

Abstract: Performing a probabilistic assessment of a building component can easily become computationally inhibitive.To solve this issue, the hygrothermal model can be replaced by a metamodel, which mimics the original model with a strongly reduced calculation time. In this paper, convolutional neural networks are used to predict hygrothermal performance. Because neural networks do not extrapolate well outside their training subspace, it is important to select the training data wisely so that the network can be used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…To reduce simulation time, this study proposes the use of a metamodel, a mathematical model that replaces the original hygrothermal model. The authors showed previously that a convolutional neural network is able to accurately capture the non-linear hygrothermal response of a massive masonry wall [6]- [8] and thus is likely to be suitable for timber frame wall simulations as well. The neural network is trained on a limited dataset, obtained with the original hygrothermal model.…”
Section: Convolutional Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce simulation time, this study proposes the use of a metamodel, a mathematical model that replaces the original hygrothermal model. The authors showed previously that a convolutional neural network is able to accurately capture the non-linear hygrothermal response of a massive masonry wall [6]- [8] and thus is likely to be suitable for timber frame wall simulations as well. The neural network is trained on a limited dataset, obtained with the original hygrothermal model.…”
Section: Convolutional Neural Networkmentioning
confidence: 99%
“…The authors showed previously that a convolutional neural network for time series is highly adequate for such purpose [6]- [8] as it is able to capture the complex time-dependent patterns of the hygrothermal response and allows flexibility in the desired post-processing. Hence, a similar network architecture as in [6] is used in this study to replace the hygrothermal model used to evaluate the hygrothermal performance of timber frame walls.…”
Section: Introductionmentioning
confidence: 99%
“…Various hygrothermal simulation programs emerged alongside the maturation of theoretical frameworks [11][12][13]. Hygrothermal simulation programs were frequently combined with a stochastic approach [14,15] or machine learning [16][17][18][19] to simulate and predict the envelope's long-term condition and function. The hygrothermal simulation software, especially Wärme Und Feuchte Instationär (WUFI), was used to evaluate the suitability and hygrothermal properties of new materials.…”
Section: Introductionmentioning
confidence: 99%
“…The hygrothermal response of building components is transient and highly nonlinear. Astrid et al [28][29][30] developed a meta-model to replace the hygrothermal model, and hygrothermal time series such as temperature, humidity, and moisture content can be directly predicted. The network reliably evaluated the future damage risks of walls and calculated the hygrothermal performance of 96 types of wood-frame walls.…”
Section: Introductionmentioning
confidence: 99%